ENSURING THE CONTINUITY OF FAMILY LAW PROTECTION AFTER THE OPENING OF SUCCESSION ESTATE IN RUSSIAN LAW - Đokić, Ivana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
In modern Russian succession law, factual grounds (incapacity for work, maintenance and community of life with the testator, etc.) have a decisive influence on the construction of the legal and necessary hereditary order. Thus, the Russian legislator protected incapable persons who were, after the death of the provider, supported by the testator during his lifetime. By enacting such inheritance regulations, the legislator has remained faithful to the Russian legal tradition and the idea of subsistence (which is the basis of legal inheritance in Russian law), and successfully ensured the continuity of family law protection for incapacitated individuals. This paper focuses on the inheritance mechanism aimed at ensuring the continuity of family law protection to persons who are incapable to work, and who were supported by the testator during his/her lifetime. In light of current inheritance legislation of the Russian Federation and the views presented in the Russian legal literature and jurisprudence, the author points out that the continuity of family law protection of incapacitated persons who were supported by the testator may be effectively ensured through the institute of universal succession.
Keywords: inheritance; incapacity for work; subsistence; community of life